Assessing the optimal capital structure: A case study of Afren public limited company - a small exploration and production oil and gas company - Osinubi, Tokunbo S.; Amaghionyeodiwe, Lloyd; Okoye, Chikaodili C. (Journal of Management, Economics, and Industrial Organization, 2019)
This study assessed the optimal financing mix for Afren Public Limited Company based on the trade-off theory and evaluated the cost to the firm from deviating from that position. In doing this, we derived a firm-specific optimal capital structure using the cost of capital approach, which involved the use spreadsheet modelling through an iterative process to determine series of discount rates based on different combinations of debt and equity under the assumption of constant earnings to the firm. The base result shows that as the debt intensity increases, the equity Beta has a multiplier effect such that the cost of equity increases more than proportionately to the increase in leverage. As more debt is introduced, the risk of loan default increases, thus increasing the credit spread over the riskless rate and effectively the pre-tax cost of debt. The result from the firm’s weighted average cost of capital (WACC) and value as a function of leverage, implied optimal debt ratio is 40% and yields a WACC of 8.63% which is effectively the minimum cost of capital that maximizes the value of the firm. Between 40% and 45% leverage, the debt servicing capacity of the firm measured by the interest coverage ratio drops significantly from 4.6 to 1.4 due to high interest burden. This increased credit risk has a direct impact on the firm’s credit quality rating.